POLA HIDUP CERDIK HINDARI KANKER & DETEKSI DINI KANKER PADA PEREMPUAN DI RT 16-18 DESA PENYENGAT OLAK KABUPATEN MUARO JAMBI 2018 - Ajeng Galuh Wuryandari; Indarmien Netty Ariasih; Supatmiyati Supatmiyati (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2019)
The national program for Early Cancer Prevention Movement for Indonesian Women 2015-2019 is being carried out throughout Indonesia. The Indonesian Cancer Foundation (YKI) is a non-profit organization that is working socially and humanitarian in health concern, especially in cancer prevention. YKI has several informative media to help increase the knowledge and awareness of the importance of preventing cancer, one of which is a brochure that contains information about a healthy lifestyle preventing cancer with